Buying Interest, Attitude, and Maqasid Sharia - Zulpahmi,; Sumardi,; Rahmah, Yasinta (The journal of contemporary issues in business and government, 2021)
This study aimed to analyze the buying interest factors of Samyang products by using attitude as an intervention factor based on maqasid sharia. Data were collected using questionnaires. The type of this study was quantitative using a purposive sampling technique. The applied data analyses were validity, reliability, classic assumption, and statistical tests using path analysis. The results indicated that product knowledge and price had a positive and significant effect on attitude. Meanwhile, halal certification and halal awareness do not affect attitude. Furthermore, the price and attitude had a positive and significant effect on buying interest. Meanwhile, product knowledge, halal certification, and halal awareness do not affect buying interest. Attitude can mediate product knowledge and prices towards the buying interest of Samyang products. Besides, the results of the hypothesis using the F-test showed that the product knowledge, halal certification, halal awareness, price, and attitude simultaneously had a positive effect on buying interest.